Effect of climatic factors on wheat grain quality - Szabó P. Balázs; Véha Antal; Gyimes Ernő (2013)
Quality in general is the sum of characteristics. In this work factors of complex quality have been examined. The factors, which determine the wheat quality, can be sorted into two groups, the natural factors and the growing factors. The natural factor (rain full, temperature, air) determines the varieties and the growing technology. The growing factor (variety, seed corn, sowing-time, nutrients etc.) determines the profit. The wheat was harvested at two different times, and they were grown by the same agro technological treatments. Before the harvest we examined the kernel, we get information about the possible injury. After the harvest we examined the gluten characteristic, the alveograph and valorigraph behaviors. The effects of varieties were dominated, but there was a full of meaning the weather, because the harvest was drawn away so the plant gave a lot of rain. Yield is an economic index and it is a connection with the kernel hardness, the order of the varieties shows it. In this study we examined these parameters, and the connection among these factors.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok; Mezőgazdaság-tudományok; Mezőgazdaság, erdészet, halászat